Whirlwind Rolling Process of Slender Shaft - Zhang Hong; Deng ZhiPing; Jin Long; Long Jun; Zhang Zhengyi (Institute of Advanced Engineering and Science, 2013)
In order to solve the problem of slender shaft which is easy bended and deformed for its big slenderness ration and poor rigidity, the method of whirlwind rolling with Tri-tools is designed. This paper introduces the principle and the process of stress analysis. With the help of ABAQUS finite element simulation software, the 3D model of whirling rolling is established. The rolling process is simulated by the software and summarizes the influence of quality factors during the whirlwind rolling process. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2554